Analisis Rasio Solvabilitas Untuk Menilai Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia 2019-2023 - Asmaranda Kumay; Ilyas Lamuda; Zubaidah Rahman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the level of solvency as an indicator of financial performance at PT Mustika Ratu Tbk and PT Martina Berto Tbk during the 2019–2023 period. The method used is a descriptive quantitative approach, utilizing secondary data obtained from the companies' annual financial statements published through the Indonesia Stock Exchange and the official websites of each company. Data analysis was conducted by calculating and evaluating solvency ratios, including the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Times Interest Earned (TIE). The results indicate that both companies exhibit high DAR values, suggesting a significant dependence on debt. Nevertheless, the DER values reflect a relatively healthy and controlled capital structure. PT Mustika Ratu Tbk is considered to be more capable of managing its long-term obligations compared to PT Martina Berto Tbk, which shows signs of financial pressure due to a high proportion of long-term debt.